“PARABASIS IN NIKOLAY GOGOL’S THE INSPECTOR GENERAL": THE PROVERBIAL MEDIUM - McKenna, Kevin J. (Proverbium - Yearbook, 2014)
While not attached to the original 1836 text of his play, The Inspector General, Nikolay Gogol appended the famous proverb-epigraph “Don’t grumble at the mirror if your [own] puss is distorted” to the 1842 edition of his comedy, which he recognized as the final and definitive version. Fond of the pithy folk language of both Russia and his native Ukraine, it is not surprising that he would do so. In addition, this proverb-epigraph captures the moralistic message that Gogol clear-ly intends to impart to his readers, a message that the Mayor blasts to his audience in the closing scene of Act Five. In light of his fondness for Aristophanic Comedy, however, Gogol may have had another pur-pose in mind as he opened the 1842 version of his play with this famous Russian proverb. The Russian literary critic Vyacheslav Ivanov first called attention to this aspect of Gogol’s play early in the last century, when he made an argument for the Mayor’s outburst at the close of Act Five as a parabatic statement in the style of the Old Comedy of fifth-century Greece (B.C.). While acknowledging the genius of Ivanov’s analysis of the play, the present article departs from his conclusion that this outburst represents the central parabatic moment in the play. Instead, a case is made for considering the proverb-epigraph that opens Gogol’s play as either the main parabasis or, at least, as one that is parallel, perhaps a prequel to the Mayor’s famous address to his audience at play’s end.